Hardiness And Its Relationship With Psychological Qualities - pcadmin, Mannabova Ezoza (Genius Publishing Group, 2025)
Hardiness is a person’s ability to overcome difficulties that arise in the process of achieving their goals. Problems that can arise with low life expectancy include: increased stress levels, depression, apathy, deterioration of physical health, decreased interpersonal relationships and productivity. In severe cases, this can lead to suicide. From this point of view, we set ourselves the task of identifying psychological qualities that affect the work of students in the Uzbek environment
Keywords: Hardiness; Commitment; Control